Tourism development in the North Caucasus Federal District - V. V. Stroev; M. D. Magomedov; E. Yu. Alekseycheva (Вестник университета, 2023)
The article shows the great importance of tourism development for the economy of the Russian Federation. Attention is drawn to the availability of favorable conditions for this industry in the North Caucasus Federal District of the country. The tourism development potential is considered in detail in each subject of the studied district (Stavropol Territory, the Republic of Dagestan, the Chechen Republic, the Republic of Ingushetia, the Kabardino-Balkarian Republic, the Karachayevo-Cherkessian Republic, The Republic of North Ossetia-Alania), and the circumstances hindering this process have been identified. The main directions of tourism development in the subjects of the North Caucasus Federal District are substantiated, such as growth of highly qualified specialists in tourism organization; construction of hotels; infrastructure development; increasing the number of catering facilities; improving the quality of transport services; conducting marketing research aimed at the tourism development of various directions; effective pricing policy for tourist services.